Steel bridge long-term performance research technology framework and research progress. Issue 1 (January 2017) - Wang, Chunsheng; Duan, Lan; Zhai, Musai; Zhang, Yuxiao; Wang, Shichao
To ensure structural sustainability, it is necessary to conduct steel bridge long-term performance study, including bridge design, evaluation, maintenance, and reinforcement technology. The research on steel bridge long-term performance is introduced in four aspects: (1) fatigue performance experimental study for full-scale orthotropic steel bridge decks in laboratory to study its fatigue failure mechanism, in order to improve fatigue design methodology and find rational reinforcement and maintenance method; (2) conducting steel bridge out-of-plane distortion-induced fatigue performance study, and developing cold reinforcement method; (3) performance study for base material and typical joint under long-term vehicle and environmental effect in aging steel bridges, and safety assessment and maintenance of existing steel bridge; (4) temperature gradient monitoring for steel box girder model to build the temperature design mode. Meantime, in-situ tests and monitoring are conducted for steel bridge long-term performance detection, assessment, and maintenance. The study results in this article build the research framework of steel bridge long-term performance preliminarily, which is the basis for steel bridge sustainable design, maintenance, and cold reinforcement methodology system.